2011
DOI: 10.1128/mcb.00581-10
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a Regulates Beta Cardiac Myosin Heavy Chain Gene Expression by Targeting Thyroid Hormone Receptor β1 in Neonatal Rat Ventricular Myocytes

Abstract: MicroRNAs (miRNAs), small noncoding RNAs, are negative regulators of gene expression and play important roles in gene regulation in the heart. To examine the role of miRNAs in the expression of the two isoforms of the cardiac myosin heavy chain (MHC) gene, ␣-and ␤-MHC, which regulate cardiac contractility, endogenous miRNAs were downregulated in neonatal rat ventricular myocytes (NRVMs) using lentivirus-mediated small interfering RNA (siRNA) against Dicer, an essential enzyme for miRNA biosynthesis, and MHC ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 52 publications
5
59
1
1
Order By: Relevance
“…In addition, microRNA-27a was demonstrated to modulate the cardiac β-myosin heavy chain gene via thyroid hormone signaling (14). Li et al confirmed that antisense microRNA-27a and overexpression of ZBTB10 blocked estrogen-induced transactivation in breast cancer (15).…”
Section: Introductionmentioning
confidence: 55%
“…In addition, microRNA-27a was demonstrated to modulate the cardiac β-myosin heavy chain gene via thyroid hormone signaling (14). Li et al confirmed that antisense microRNA-27a and overexpression of ZBTB10 blocked estrogen-induced transactivation in breast cancer (15).…”
Section: Introductionmentioning
confidence: 55%
“…However, transplanting iPSC-CMs into the heart induced a transition from the β to the α MHC isoform, a transition seen during cardiac development and maturation. 35 Although this study did not investigate changes in mitochondrial quantity or structure in iPSC-CMs after transplantation into the heart, the maturing of MHC after transplantation implies a functional imjunctions with the basement membrane, possibly enhancing the integration of transplanted iPSC-CMs into the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of miR-133a expression results in ectopic expression of smooth muscle genes in the heart and aberrant cardiomyocyte proliferation (8). Targeted deletion of miR-126 displays defective cardiac neovascularization in mice that survive myocardial infarction (14); miR-206 is involved in apoptotic cell death in myocardial infarction by post-transcriptional repression of IGF-1 (15); and miR-27a regulation of β-MHC gene expression by targeting TRβ1 has been identified in cardiomyocytes (16). Other differentially expressed miRNAs between SV and control cardiac tissues were not investigated and further research is required to evaluate their roles in cardiac development.…”
Section: Discussionmentioning
confidence: 99%